Impact of corporate donations to combat Covid-19 on the market value of donor companies: an analysis from the perspective of legitimacy theory - João Henrique Krauspenhar; Rafael Bertoldi Pescador; Suliani Rover; Denize Demarche Minatti Ferreira; Hans Michael Van Bellen (Revista Ambiente Contábil)
Purpose: The objective of the study is to verify the impact of corporate donations aimed at combating Covid-19 on the market value of the involved companies.